2019
DOI: 10.1186/s13048-019-0519-z
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates palmitic acid-induced mouse granulosa cells apoptosis via endoplasmic reticulum stress

Abstract: Background Palmitic acid (PA), the main component of dietary saturated fat, causes apoptosis in many cell types, including mouse granulosa cell. Melatonin, an important endogenous hormone, has beneficial effects on female reproductive processes. Since elevated PA levels are present in follicular fluid (FF) of patients with infertility and are shown to be toxic for granulosa cells, we investigated the molecular mechanisms of PA toxicity in mouse granulosa cells and explored the effects of melatonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…The reason may be that 500 mg/kg of quercetin is far beyond the effective range of quercetin to exert its role. Correspondingly, it has been demonstrated in other antioxidant studies that antioxidant effects are in a dose-dependent manner [28,29]. The present results will provide reference for the use of quercetin as a feed additive to protect broiler intestinal health.…”
Section: Discussionsupporting
confidence: 75%
“…The reason may be that 500 mg/kg of quercetin is far beyond the effective range of quercetin to exert its role. Correspondingly, it has been demonstrated in other antioxidant studies that antioxidant effects are in a dose-dependent manner [28,29]. The present results will provide reference for the use of quercetin as a feed additive to protect broiler intestinal health.…”
Section: Discussionsupporting
confidence: 75%
“…This indicates that elevated concentrations (> 100 μM) of SFAs are cytotoxic to human GCs. Similar negative effects of SFAs have been reported in mice, cows, and pigs [30,38]. Shibahara et al 2020 [39] have recently reconfirmed the proapoptotic effects of SFAs as they observed induced expression of caspase-3 and C/ EBP homologous protein (CHOP) and decreasing Akt phosphorylation in porcine GCs.…”
Section: Saturated Fatty Acidsmentioning
confidence: 58%
“…Multiple studies have indicated that melatonin grants protective effects on ovarian follicles against the toxicity induced by gonadotoxic agents such as palmitic acid (PA), Di (2-Ethylhexyl) phthalate, and nicotine. [39][40][41][42] Melatonin's proposed protective benefits are based on documentation of inhibition of ER stress, reduction of reactive oxygen species (ROS) levels, and inhibition of apoptosis. Previous literature 26,27 indicated that melatonin significantly decreased the cisplatin-mediated phosphorylation of PTEN, AKT, and translocation of FOXO3a from the nucleus to cytoplasm in primordial oocytes, blocking the activation of primordial follicles in the mouse ovary.…”
Section: Discussionmentioning
confidence: 99%